2021
DOI: 10.1186/s12889-021-11804-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with duration of breastfeeding in Bangladesh: evidence from Bangladesh demographic and health survey 2014

Abstract: Background Breastfeeding for optimum duration is one of the most effective ways to reduce infant morbidity and mortality and confirms expected growth and development of children. The aim of this study was to determine the effect of socio-demographic and anthropometric determinants on duration of breastfeeding (DB) among mothers in Bangladesh. Methods The data was extracted from the Bangladesh Demographic and Health Survey (BDHS)-2014. A total of 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…Our bivariate analyses also indicate that BMI is significantly and positively associated with age and educational attainment (of both women and their partners), which is in line with recent studies from Bangladesh [8082]. We find that breastfeeding women have a lower BMI than their non-breastfeeding counterparts, which (i.e., the protective effect of breastfeeding against high BMI) is also in line with studies in Bangladesh and elsewhere [8386].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our bivariate analyses also indicate that BMI is significantly and positively associated with age and educational attainment (of both women and their partners), which is in line with recent studies from Bangladesh [8082]. We find that breastfeeding women have a lower BMI than their non-breastfeeding counterparts, which (i.e., the protective effect of breastfeeding against high BMI) is also in line with studies in Bangladesh and elsewhere [8386].…”
Section: Discussionsupporting
confidence: 91%
“…that breastfeeding women have a lower BMI than their non-breastfeeding counterparts, which (i.e., the protective effect of breastfeeding against high BMI) is also in line with studies in Bangladesh and elsewhere [83][84][85][86].…”
Section: Discussionsupporting
confidence: 86%
“…In addition to the lack of nurseries in the mother's workplace, making it difficult for working women to breastfeed their infants ( 22 ). Previous studies have also reported that maternal employment was negatively associated with exclusive breastfeeding ( 16 , 48 50 ). However, this study showed that women living in Sharjah were more committed to EBF than those living in Dubai.…”
Section: Discussionmentioning
confidence: 83%
“…This underscores the necessity of targeted interventions promoting comprehensive sexuality education, delaying childbearing, and ensuring equitable access to family planning services for young people [8]. The negative association between educational attainment and unintended abortion mirrors prior studies in Bangladesh [4,10]. Education empowers women with knowledge about reproductive health and contraceptive options, enabling them to make informed choices about their fertility [8].…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have explored the factors associated with unintended abortion in Bangladesh, identifying sociodemographic characteristics, economic factors, and healthcare access as key contributors [4]. However, a complete understanding of the complex interplay between these factors and their relative importance in different contexts is still needed.…”
Section: Introductionmentioning
confidence: 99%